2015
DOI: 10.5751/es-07172-200110
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable livelihoods through conservation of wetland resources: a case of economic benefits from Ghodaghodi Lake, western Nepal

Abstract: ABSTRACT. We investigated the participation of local ethnic groups in wetland conservation, determined the economic benefits that they received from the wetlands, and assessed socioeconomic factors that affect dependency on wetlands. A total of 217 wetland resource-user households residing around Ghodaghodi Lake, western Nepal were surveyed. Data were analyzed using descriptive statistics, t-tests and ordinary least squares regressions. The wetland resources contributed significantly to the household economy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 32 publications
6
51
0
5
Order By: Relevance
“…For instance, the average annual home stay income for the year 2011 was US $2,000, and US $1,250 per household in the Bo Lu and Pac Ngoi villages, respectively, from Ba Be wetland tourism in Vietnam (Ramsar and UNWTO, 2012). In their study, Lamsal et al (2015b) reported positive attitudes and willingness of local people to participate in community-based conservation activities at the GLC. We anticipate that this positive attitude and willingness of local people should be taken as a good opportunity by concerned agencies to facilitate community participation in tourism and nature conservation programme at this Ramsar Site.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, the average annual home stay income for the year 2011 was US $2,000, and US $1,250 per household in the Bo Lu and Pac Ngoi villages, respectively, from Ba Be wetland tourism in Vietnam (Ramsar and UNWTO, 2012). In their study, Lamsal et al (2015b) reported positive attitudes and willingness of local people to participate in community-based conservation activities at the GLC. We anticipate that this positive attitude and willingness of local people should be taken as a good opportunity by concerned agencies to facilitate community participation in tourism and nature conservation programme at this Ramsar Site.…”
Section: Discussionmentioning
confidence: 95%
“…In their study, Lamsal et al . () reported positive attitudes and willingness of local people to participate in community‐based conservation activities at the GLC. We anticipate that this positive attitude and willingness of local people should be taken as a good opportunity by concerned agencies to facilitate community participation in tourism and nature conservation programme at this Ramsar Site.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the findings of Lamsal et al (2015), who reported wetland income from Ghodaghodi Lake, western Nepal was not affected by education of respondents. Adams and Hulme (2001) argued "community conservation is not one thing but many" and highlighted the range of mechanisms that can be used to bridge livelihood activities with conservation objectives.…”
Section: Discussionsupporting
confidence: 92%
“…Park managers can also use this information in planning and finding the most appropriate management strategies to implement for the park. Furthermore, Lamsal et al (2015) suggested that better-off households who had less dependence on wetland resources were more involved with conservation organisations. A similar contribution of linkages between less direct benefits of wildlife management areas and more direct engagement with policy process was found in northern Tanzania by Salerno et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation